In Ballast to the White Sea - Lowry, Malcolm, 1909-1957 (Book collections on Project MUSE., 2014)
This is the first edition of In Ballast to the White Sea, the autobiographical novel by Malcolm Lowry, known to most only through the highly romanticized story of its loss in a fire. In fact, the typescript itself has probably been read by at most a dozen people since Lowry scholars learned that it was deposited at the New York Public Library.